Purification and characterization of glutaminase and urease-free L-asparaginase from Bacillus atrophaeus with acrylamide reduction potential (International Journal of Biology and Chemistry, 2024)
L-asparaginase (L-asnase) is a versatile enzyme with uses in food industry and medicine. Current study aimed to isolate L-asnase producing microorganism/s without urease and glutaminase and optimize L-asnase production. First, screening and isolation of L-asnase-producing bacterial strains that did not produce glutaminase and urease from chicken gizzards were performed. For this purpose, the enzyme producing bacteria were screened on the agar medium supplied with substrate and phenol red indicator dye. Among the isolated bacteria, 1 isolate showed L-asnase free of glutaminase and urease. The selected strain was identified by biochemical, morphological and 16s rRNA sequencing. The selected strain was identified as Bacillus atrophaeus by 16S rRNA sequencing. The effects of incubation temperature (30°C) and time (72 hours), medium pH (8.0) and nutritional sources (glucose and NaNO3) on L-asnase production were determined. L-asnase was purified with acetone, and its molecular weight was determined to be 42 kDa by SDS-Page. Enzyme kinetics were also calculated, and it was determined that Vmax was 43 μmol/mL/min and Km was 2.7 mM. L-asnase activity was highest at 40 ℃ and the optimal pH was 8.0. L-asnase activity was stimulated by Mn2+, Mg2+, and Ca2+ but inhibited by Co2+, Na+, Zn2+, and Hg2+. L-asnase was utilized to treat potato chips before they were fried in order to assess its capacity to mitigate acrylamide. The result was an 80% reduction in acrylamide concentration when compared to the untreated control. Based on these findings, it appears that L-asnase could have potential use in the food industry.